A Scoping Review of Factors Associated with Self-Management Among Patients with Breast Cancer - Ruth Jamlaay; Restuning Widiasih; Mira Trisyani (Journal Of Nursing Practice, 2025)
Self-management in patients with breast cancer plays an essential role in improving the quality of life of breast cancer patients. Self-management behaviour changes along with the treatment period and varies in patients with different demographic and psychosocial characteristics. However, systematic identification of self-management factors in this population is still lacking. This review aimed to identify factors that influence self-management in patients with breast cancer. This study used a scoping review. Literature was searched from three databases: EbscoHost: Medline Ultimate, Pubmed, and Scopus, and additional literature was identified using Google Scholar, using the keywords "Self-management OR self-care AND breast cancer OR breast neoplasm OR breast tumours AND factors or causes or influences or reasons or determinants or predictors or contributors." The analysis was carried out thematically with a descriptive exploratory approach. A total of 11 articles were analyzed in this review. Several factors influence self-management in patients with breast cancer, including chemotherapy status, duration of illness, patient's personal experience, age, education level, social support, anxiety, self-efficacy, self-compassion, understanding of the condition, adaptation and acceptance of life with lymphedema. This findings underscore the importance of developing comprehensive interventions that address these diverse factors to enhance self-management. These interventions should include patient education, psychological support, and social assistance to improve patients' ability to manage their condition. A holistic approach, incorporating medical care, emotional well-being, and social support, is essential to improving the overall quality of life for breast cancer patients.